Association between Optical Coherence Tomography Measurements and Clinical Parameters in Idiopathic Intracranial Hypertension - Priscilla Fernandes Nogueira; Gustavo Coelho Caiado; Carolina P. B. Gracitelli; Fernando Meister Martins; Felipe Chaves Duarte Barros; Sandro Luis De Andrade Matas; Sérgio Henrique Teixeira; Luciana da Cruz Noia; Danilo Andriatti Paulo (Journal of Ophthalmology)
Purpose. To correlate optical coherence tomography (OCT) measurements with clinical parameters in idiopathic intracranial hypertension (IIH). Methods. A cross-sectional study was conducted with 22 patients with IIH and 11 controls. All participants underwent comprehensive ophthalmological examination followed by spectral-domain OCT (SD-OCT) and standard automated perimetry using the 30–2 program of the Humphrey visual field analyzer. Correlations between ganglion cell complex (GCC) thickness and retinal nerve fiber layer (RNFL) thickness, as measured by SD-OCT, and clinical parameters were assessed using generalized estimating equations. Result. The mean age of the participants was 35.0 ± 10.83 years. The groups were similar regarding age, but were significantly different regarding sex and visual acuity (p=0.001 and p=0.038, respectively). The GCC was significantly thinner in the IIH group, with a mean of 90.535 ± 9.766 μm compared to 98.119 ± 6.988 μm for the controls (p=0.023). There was a significant association between GCC thickness and optic disc pallor (p=0.016) and between edema and visual acuity (p=0.037). No significant difference was found in RNFL thickness between patients and controls. Conclusion. The GCC was thinner in the patients with IIH compared to the controls, and there was an association between GCC and optic disc pallor. This might suggest a role for OCT parameters when the structural changes that occur in IIH are investigated, possibly guiding clinical decision making.